El impacto en los ciudadanos colombianos por cuenta de los créditos con interés alto que el sector financiero ofrece actualmente. (2023)
This research deals with the impact of high-interest loans on the personal economy of Colombian citizens, since around 2020 when the pandemic - COVID 19 arrived in the country many of the people who had credits with a bank for one or For another reason, they entered into default, even clients who had not presented this behavior throughout their credit life, since due to the health emergency many of those who had establishments had to close them or in another case the companies had to cut staff since there was not much liquidity present. Due to the above, financial entities were forced to implement new financial circulars issued by the Banco de la República, where its main objective was to grant grace periods in the different financial products, in order to mitigate the economic impact that the crisis in the client's pockets with financial relief. Throughout this investigation, it will be concluded if this financial relief really favored the citizens who accepted this grace period, or on the contrary, there was no benefit of any kind. For this reason it is important to have an adequate financial education that allows them to make better decisions that ultimately favor the stability and development of an economic system.